2019
DOI: 10.1155/2019/7376903
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic and Endoscopic Cooperative Dissection for Small Gastric Gastrointestinal Stromal Tumor without Causing Injury to the Mucosa

Abstract: Objective. To investigate the feasibility of laparoscopic and endoscopic cooperative dissection (LECD) for small gastric gastrointestinal stromal tumors (GISTs) without causing injury to the mucosa, compared with ESD surgery which is widely used now. Methods. A total of 25 patients with small gastric GISTs who underwent LECD and 20 patients with small gastric GISTs who underwent ESD between October 2014 and June 2016 were included in this study. All patients underwent curative resection for pathologically diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…The drawbacks of LECS are considered the approach to only small lesions and the potential risk of gastric tumor cells spilling into the abdomen because during the procedures the gastric wall may be opened [67,68]. Some modifications to LECS were described, like inverted LECS [69], non-exposure technique (CLEAN-NET) [70], endoscopic full-thickness resection [71], and closed-LECS [72,73]. Despite the fact that there are many reports on LECS procedures which affirm the safety and efficacy of the technique, to date there is not clear evidence to perform GGs resection using LECS.…”
Section: Discussionmentioning
confidence: 99%
“…The drawbacks of LECS are considered the approach to only small lesions and the potential risk of gastric tumor cells spilling into the abdomen because during the procedures the gastric wall may be opened [67,68]. Some modifications to LECS were described, like inverted LECS [69], non-exposure technique (CLEAN-NET) [70], endoscopic full-thickness resection [71], and closed-LECS [72,73]. Despite the fact that there are many reports on LECS procedures which affirm the safety and efficacy of the technique, to date there is not clear evidence to perform GGs resection using LECS.…”
Section: Discussionmentioning
confidence: 99%
“…The main study characteristics are shown in Table 1 [ 14 , 17 , 19 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ]. Most of the studies (23) were from Asia (96%) and 22 studies (92%) were single-center.…”
Section: Resultsmentioning
confidence: 99%
“…Three studies compared the outcomes of LECS and ESD in gastric lesions [ 30 , 33 , 38 ]. In meta-analysis, R0, procedure time, hospitalization time, and adverse events were not significantly different between the two groups (shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations